The Effectiveness of a Psychoeducation Program based on Cognitive Behavioral Therapy in Developing Emotional Regulation Skills and improving Psychological Adjustment among University Students in Jeddah (The International Journal for Scientific Research, 2024)
The current study aimed to reveal the effectiveness of a psycho-education program based on cognitive-behavioral therapy in developing emotional regulation skills and improving psychological adjustment among a sample of female students at King Abdulaziz University. To achieve this objective, a quasi-experimental approach was implemented with a control and experimental groups. The study sample consisted of (14) female students from specializing in Bachelor of Psychology, as well as Master’s and Doctorate in Educational Guidance and Counseling. The quasi-experiment first consisted of distributing the members of the study sample into two groups. The experimental group of (7) female students, on whom a psycho-education program based on the theory of cognitive behavioral therapy was applied for (6) weeks, with two sessions per week. Second, a control group consisted of (7) female students, to whom the program was not applied. To study the effectiveness of the program, the performance of members of the experimental and control groups was measured on the emotional regulation scale and the psychological adjustment scale before and after the counseling intervention. The results of the current study showed that there was no effect of the counseling program in the post-measurement on the emotional regulation scale and the psychological adjustment scale, while it showed that there was an effect of the counseling program in the follow-up measurement on the emotional regulation scale.
Keywords: Emotional Regulation; Psychological Education; Psychological Adjustment